Karnataka State :5th State Finance Commission Report for the year 2024 -25 - Narayanaswamy .C , Mohamed Sanaulla, Phonde .R.S. (Karnataka Karnataka State Finance Commission, 2024)
Report for the year 2024 - 25
Keywords: Fifth State Finance Commission Report of Karnataka